PENINGKATAN KOMPETENSI GURU DALAM IMPLEMENTASI METODE PEMBELAJARAN BERBASIS PAIKEM DI UPT SD NEGERI SIDOREJO 01 DOKO - Ma’rufi, Ahmad; Inayati, Isna Nurul (INCARE, International Journal of Educational Resources, 2022)
The development of science and technology encourages educational actors to always innovate learning so that students are able to think critically, creatively, innovatively, collaboratively, and communicatively. Increasing teacher competence is certainly needed in carrying out the intended learning innovation. To improve teacher competence in implementing PAIKEM-based learning, this school action research is intended to be carried out. This research was conducted at SDN 01 Sidorejo in November 2021 with the research subjects being all 10 teachers of SD Negeri Wonodadi 01. The technique of collecting data from this school action research is through qualitative data obtained from observations, interviews and document studies. This school action research was carried out in 2 cycles. Each cycle includes the following stages: (1) planning, (2) implementation, (3) observation, and (4) reflection. The results of this school action research showed that in cycle 1 the implementation of activities reached a value of 76.6 and cycle 2 increased to 86, teacher competence in cycle 1 reached a value of 84.5 and in cycle 2 it reached 88.5. The impact of the activity on students has shown success with increasing students' abilities reaching a score of 81.25 and student wellbeing reaching 78.7. So it can be concluded that the improvement of teacher competence in the implementation of PAIKEM-based learning methods can be concluded to be successful.